1981
DOI: 10.1902/jop.1981.52.4.197
|View full text |Cite|
|
Sign up to set email alerts
|

Penetration of Dental Plaque Components Into Gingiva: Sequential Topical Treatments With Hyaluronidase and Streptococcal Polysaccharide in Rats

Abstract: EIGHTY-FIVE Sprague-Dawley rats were used in two experiments to determine the conditions necessary to permit transepithelial penetration by deleterious macromolecules in murine oral mucosa. In experiment one, Group I was a water and diet control; Group II mucosa was treated with hyaluronidase; Group III with streptococcal polysaccharide; and Group IV with hyaluronidase, followed by treatment with the polysaccharide. In the second experiment, the histological effects of the streptococcal polysaccharide were qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…non-keratinized sites which are constantly exposed to a stagnant bacterial environment. It has been suggested that the onset of periodontal disease follows the initial damage to the tissue barrier (Page and Schroeder, 1976;Rizzo, 1968;Gaffar et al, 1981). Previous studies have shown that penetration occurs by simple diffusion through the intercellular spaces of the epithelium (Tregear, 1966;Siegel et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…non-keratinized sites which are constantly exposed to a stagnant bacterial environment. It has been suggested that the onset of periodontal disease follows the initial damage to the tissue barrier (Page and Schroeder, 1976;Rizzo, 1968;Gaffar et al, 1981). Previous studies have shown that penetration occurs by simple diffusion through the intercellular spaces of the epithelium (Tregear, 1966;Siegel et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…They induce a change in the structure of the crevicular epithelial barrier to permit an increase in accessibility of microbial substances to the underlying connective tissue layer, where they initiate a sequence of destructive inflammatory reactions. The maintenance of the tissue barrier is important, since toxic substances such as endotoxin and bacterial dextrans, per se, have been shown to be incapable of causing inflammation in healthy sulcular gingiva (Gaffar et al, 1981;Rizzo, 1968). …”
Section: Introductionmentioning
confidence: 99%
“…Second, during the active stages of gingivitis and periodontitis, bacteria from the subgingival plaque have been shown to invade the tissues of the periodontium (11)(12)(13)(14)(15)(16). The plaque organisms etnit metabolic products such as toxins, enzymes and poiysaccharides which initiate or cause destructive changes in the gingiva (13,(17)(18)(19) and allow penetration of the bacteria deeper into the connective tissues. Third, bacteretnias have been reported to occur immediately following dental manipulation such as tooth extractions, periodontal and root treatment (20)(21)(22) or even following tooth brushing (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Dental plaque is an etiologic factor in the development of chronic periodontal disease, which can eventually lead to tooth loss if untreated . Plaque tends to accumulate on proximal surfaces, i.e., the locations between teeth.…”
mentioning
confidence: 99%